THE IMPLEMENTATION OF EXPEDITIONARY LEARNING INTEGRATED WITH MULTIPLE INTELLIGENCES AND LOCAL WISDOM - Muhammad Reza Ainun Najib; Yan Imam Santoso; Madya Giri Aditama; Saiful Risqi; Sintia Oktaviani (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2026)
Conventional cognition-oriented learning models are considered less able to respond to the demands of 21st century learning, so a more holistic, contextual, and student-centered approach is needed. This study aims to explore teachers' experience in implementing the Expeditionary Learning model integrated with Multiple Intelligences and local wisdom in English language learning in high schools and vocational schools in Batang Regency. Using a phenomenological qualitative approach, data were collected through observation, questionnaires, interviews, documentation, and FGD of 25 teachers who were selected purposively. The results showed that the mapping of multiple intelligences identified the dominance of kinesthetic, visual-spatial, and linguistic intelligence, which teachers then translated into various expedition projects such as industrial expeditions and local product (UMKM) promotion (48%), folklore dramas and traditional games (36%), and tourism promotions (16%). This authentic experiential learning has been shown to increase students' motivation, creativity, participation, and English language competence while strengthening their cultural identity. The research concludes that the integration of EL–MI–local wisdom is an effective pedagogical approach to creating relevant, humanistic, and contextual learning, and recommends further exploration in more diverse school contexts to broaden the generalization of findings.